Conversion of Jatropha curcas Oil to Ester Biolubricant Using Solid Catalyst Derived from Saltwater Clam Shell Waste (SCSW) - Said, N.; Fatimah A., Misebah; R. M., Yunus; Mohd S., Mahmud; Ahmad Z., Sulaiman (World Academy of Science, Engineering and Technology, 2014)
The discarded clam shell waste, fossil and edible oil as biolubricant feed stock couse environment issues and food chain dilemma, thus this wok aim to solve this problem by using activated saltwater clam shell waste (SCSW) as solid catalyst for conversion of Jatropha curcas oil as non-edible sources to ester biolubricant. The characterization of solid catalyst was done by DTA-TGA, XRF, XRD, BET, FESEM and FTIR analysis. The calcined catalyst was used in the transesterification of Jatropha curcas oil to methyl ester as the first step, and the second stage was involved the reaction of Jatropha methyl ester (JME) with trimethylolpropane (TMP) based on the various process parameter. The formated biolubricant was analyzed using the capillary column (DB-5HT) equipped GC. The maximum results of Jatropha oil conversion to ester biolubricant was 96.66% with 72.3% of trimetylolpropane triester (TMPTE) composition.